Securities Acceptable to the Lending Banker - Mather, L. C. (London : Waterlow, 1966)
This book has been produced in response to many requests from readers of The Bankers' Magazine who found the original articles helpful in their daily work. It completes the series of four volumes covering the field of practical banking.
Includes index
osc 15/08/17
Loans
Keywords: Security (Law); Bank loans